2020
DOI: 10.3390/vaccines8030428
|View full text |Cite
|
Sign up to set email alerts
|

Protective Immunity Induced by Virus-Like Particle Containing Merozoite Surface Protein 9 of Plasmodium berghei

Abstract: Merozoite surface protein 9 (MSP-9) from Plasmodium has shown promise as a vaccine candidate due to its location and possible role in erythrocyte invasion. In this study, we generated virus-like particles (VLPs) targeting P. berghei MSP-9, and investigated the protection against lethal doses of P. berghei in a mouse model. We found that VLP vaccination induced a P. berghei-specific IgG antibody response in the sera and CD4+ and CD8+ T cell populations in blood compared to a naïve control group. Upon challenge … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 45 publications
3
20
0
Order By: Relevance
“…Endotoxin presence in the recombinant baculoviruses was checked using Pierce™ Chromogenic Endotoxin Quant Kit (Thermo Fisher Scientific, Waltham, MA, US). To characterize the expression of ROP4 in rBVs, a polyclonal mouse anti- T. gondii antibody was used to probe T. gondii ROP4 protein in rBVs by ELISA as previously described elsewhere ( Welsh, 2011 ; Lee et al., 2020 ). Briefly, wells of 96-well plates were coated with serially diluted ROP4 rBVs overnight at 4°C.…”
Section: Methodsmentioning
confidence: 99%
“…Endotoxin presence in the recombinant baculoviruses was checked using Pierce™ Chromogenic Endotoxin Quant Kit (Thermo Fisher Scientific, Waltham, MA, US). To characterize the expression of ROP4 in rBVs, a polyclonal mouse anti- T. gondii antibody was used to probe T. gondii ROP4 protein in rBVs by ELISA as previously described elsewhere ( Welsh, 2011 ; Lee et al., 2020 ). Briefly, wells of 96-well plates were coated with serially diluted ROP4 rBVs overnight at 4°C.…”
Section: Methodsmentioning
confidence: 99%
“…In our previous study, VLPs immunizations from Toxoplasma gondii antigenic proteins or P. berghei MSP-8 and MSP-9 significantly lessened inflammatory cytokine responses [ 2 , 5 , 28 ]. Consistent with these findings, in our current study, VLP-immunized mice showed significant reductions in pro-inflammatory cytokines IFN-γ and TNF-α compared to the naïve challenge control, which may contribute to lessened parasitemia.…”
Section: Discussionmentioning
confidence: 99%
“…Plasmodium berghei ANKA strain was maintained in BALB/c mice and used for challenge infection as described previously [ 8 ]. Spodoptera frugiperda SF9 cells were used for the production of recombinant baculovirus (rBV), and virus-like particles were maintained using serum-free SF900-II medium (Invitrogen, Carlsbad, CA, USA) as described previously [ 5 ]. Plasmodium berghei -infected sera from mice were collected through retro-orbital plexus puncture.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations